Soluble Polyimides Bearing Long-Chain Alkyl Groups on Their Side Chain via Polymer Reaction - Yusuke Tsuda; Yuki Matsuda; Takaaki Matsuda (International Journal of Polymer Science)
Novel soluble polyimides having long-chain alkyl groups on their side chain were synthesized via polymer reaction with the polyimides having phenolic OH groups and 3,4,5-tris(dodecyloxy)benzoic acid (12GA) using N,N′-dicyclohexylcarbodiimide (DCC) as a dehydration reagent. The polyimides having phenolic OH groups were synthesized from the tetracarboxylic dianhydrides such as 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride (cyclohexene-DA), 4,4′-hexafluoroisopropylidendi(phthalic anhydride) (6FDA), and 3,3′,4,4′-diphenylsulfone tetracarboxylic dianhydride (DSDA) and aromatic diamines such as 4,4′-diamino-3,3′-dihydroxybiphenyl (HAB). The polymer reactions were carried out in NMP and the progresses of polymer reactions were quantitatively monitored by 1H NMR measurements (conversion; 12.2–98.7%). The obtained polyimides bearing long-chain alkyl groups have enough molecular weights, good film-forming ability, good solubility for various organic solvents, and enough thermal stability. The water contact angles of the polyimide films were investigated, and it is noted that the introduction of long-chain alkyl groups increases the hydrophobicity of polyimide surface. These polyimides are expected to be applicable as the functional materials for microelectronics such as the alignment layers of LCDs.